Energy recovery methods in adsorption refrigeration units - Grzebielec, Andrzej; Szelągowski, Adam; Ruciński, Adam (International Conference “Environmental Engineering”, 2017)
Adsorption refrigeration systems, as opposed to absorption type operate in a cyclic manner. The result is that at the beginning of each process must be fed into the adsorber state in which they will adsorb or desorb a refrigerant. In the case of two adsorbers at the start of a cycle, the one of the adsorber must be refrigerated while the second has to be heated. These processes are causing unnecessary energy loss. The aim of the work is to show how these processes can be connected and the heat received from one adsorber is transported to another adsorber. As part of the study, the heat and mass recovery processes will be considered. It turns out that in the thermal wave type systems, it is possible to recover more than 25% of the energy lost to bring the adsorber to the states in which they will operate efficiently to desorb and adsorb refrigerant. That is, it is possible to improve the efficiency of the adsorption refrigeration unit using the proposed improvements.
Keywords: refrigeration; adsorption refrigeration; energy efficiency